A Spatial Relation Model of Three-Dimensional Electronic Navigation Charts Based on Point-Set Topology Theory - Yunong Zhang; Anmin Zhang; Miao Gao; Yi Liang (ISPRS International Journal of Geo-Information, 2023)
Spatial relation models are the basis for realising three-dimensional spatial analysis. More researchers are now focusing on models that combine topological relations with distance or directional relations; however, a model that unifies all three relations has not yet been developed. In particular, it is more effective to use different spatial relations between features with different spatial characteristics in three-dimensional electronic navigation charts (3D ENC). Therefore, this paper proposes a 3D ENC feature spatial relation model (3DSRM) based on point-set topology theory, which combines 3D topological relations, distance relations and directional relations, and uses a unified model framework to describe 64 topological relations of 3D ENC features from both horizontal and vertical directions. Through the comparison and derivation of feature topological relations, it is demonstrated that the model can distinguish 3D spatial topological relations more comprehensively, realise the mutual derivation between spatial relations and spatial features, and improve the robustness of spatial relations judgement. The model can be used to judge the topological relations between features, realise 3D topological relation checking and topological creation of complex features, and improve the accuracy and interactivity of 3D ENC.